Microwave radiation imaging using inverse synthetic aperture radar technique - Ašmontas, Steponas; Kiprijanovič, Oleg; Levitas, Boris; Matuzas, Jonas; Naidionova, Irina (Elektronika ir Elektrotechnika, 2015)
Double-ridged horn antennas were used in ultra wideband radar system to create microwave radiation images. The images were obtained using inverse synthetic aperture radar technique. Transfer function of the calibrated radar system was close to one up to 22 GHz. High quality images of metallic and organic objects were created due to unique characteristic of ultra wideband radiated pulse. Metallic objects covered by visually opaque obstacles became detectable. The components of measurement set-up and the data processing are both important for the formation of these images. The obtained results confirmed the ability of ultra wideband radar to form images for various practical applications including security systems. Higher frequency of such radar system can be raised up to 40 GHz-50 GHz.DOI: http://dx.doi.org/10.5755/j01.eee.21.1.5389